Research on Robot Dynamic Path Planning Based on Multiple Linear Reinforcement Learning. Issue 1 (January 2022) - Li, Zhihong; Li, Ran; Yan, Yiying; Lu, Siyu; Gao, Yadi
Abstract: Under the background of digital and intelligent transformation, all walks of life are facing the conflict between internal stability and rapidly changing external needs, and the conflict between stable background and dynamic foreground. To solve these conflicts and problems, it needs to take new means to adjust from multiple dimensions. Draw support from the new info and communication operation support system, it could form a digital Internet info support system with the cloud platform, which can effectively establish fast and flexible front-end utilizations and support the rapid development, agile iteration and on-demand adjustment of related businesses. The Internet backbone network needs to make the info open. The new info communication operation support system based on the Internet can enable the info resources to be transmitted as needed. The research and utilization of cloud resource visualization and controllability has gradually become the key to the development of new Internet communication operation system. On the premise of systematically combing the Internet info and communication operation support system, this paper comprehensively studies the utilization of cloud resources, and analyses the utilization scenarios of cloud resources of the new education communication operation system, in order to better ameliorate the more efficient and secure utilization of cloud resources and communication operation system inside and outside the enterprise.